CLT and Task-Based Instruction for Effective Learning - Shahi, Nem Bahadur (Journal of NELTA Karnali, 2022)
The goal of Communicative Language Teaching is to develop fluency in language use. It emerged for better interaction like native speakers. Significantly, using the CLT approach increases communicative competence which is more reliable in language teaching. CLT is a broad approach to teaching that resulted from a focus on communication as the organizing principle for teaching. It helps language teachers achieve maximum learning among the learners rather than focus on mastery of the grammatical system of the languages. Task Based Instruction focuses on classroom activities involving two or more learners using communication strategies and interactional skills.